Risking capitalism - Soederberg, Susanne, 1966- (Research in political economy ;, 2016)
The growing centrality of risk management in pro-market governance raises important questions regarding how risks are produced, and why? Who and what is included in, and excluded from, risk management, and why? And, what is the relationship between the rise of risk management and neoliberalism? Drawing on various political economy approaches, this volume addresses these questions by examining - both analytically and empirically - diverse meanings and practices of risk management across a range of scales and themes ranging from austerity to climate change to housing and debt. The authors investigate the relationship between shifts in contemporary capitalism and the ways in which neoliberal forms of risk management have emerged, been reproduced and normalized, and, transformed historically.